2004
DOI: 10.1103/physreve.69.026601
|View full text |Cite
|
Sign up to set email alerts
|

Transmission properties of a single metallic slit: From the subwavelength regime to the geometrical-optics limit

Abstract: In this work we explore the transmission properties of a single slit in a metallic screen. We analyze the dependence of these properties on both slit width and angle of incident radiation. We study in detail the crossover between the subwavelength regime and the geometrical-optics limit. In the subwavelength regime, resonant transmission linked to the excitation of waveguide resonances is analyzed. Linewidth of these resonances and their associated electric field intensities are controlled by just the width of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 21 publications
2
95
0
Order By: Relevance
“…Maxwell's equations can be solved analytically for such a system (if the metal is a PEC), which is an isolated slit in a metal film, by appropriately expanding the transverse component of the field (the y component of the magnetic field, in this case) above and below the film and inside of the gap in terms of known functions and applying boundary conditions at the interfaces. While the full solution for this problem has been implicitly worked out in terms of a system of linear equations 12 , we demonstrate that under a few reasonable approximations it is possible to obtain a tractable semianalytical form for |E| 2 /|E 0 | 2 . Inside the gap E can be defined entirely in terms of its x component E x (below we will show that the z component E z is zero), which can be expanded as a superposition of forward and backwards propagating (and evanescent) waveguide modes m,…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Maxwell's equations can be solved analytically for such a system (if the metal is a PEC), which is an isolated slit in a metal film, by appropriately expanding the transverse component of the field (the y component of the magnetic field, in this case) above and below the film and inside of the gap in terms of known functions and applying boundary conditions at the interfaces. While the full solution for this problem has been implicitly worked out in terms of a system of linear equations 12 , we demonstrate that under a few reasonable approximations it is possible to obtain a tractable semianalytical form for |E| 2 /|E 0 | 2 . Inside the gap E can be defined entirely in terms of its x component E x (below we will show that the z component E z is zero), which can be expanded as a superposition of forward and backwards propagating (and evanescent) waveguide modes m,…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In particular, the functional dependence on gap size 3,5,8,9 , arguably the most basic and important aspect, has not been quantitatively determined and the underlying physical principles which determine it are not entirely known. It is the purpose of this paper to resolve this issue through finite element method (FEM) calculations 11 and an analytical theory developed for the transmission of light through an isolated slit in a metal film 12 . For two closely spaced nanostructures, the |E| 2 enhancements in the resulting gap can in principle be explained using antenna theory 13,14 , where the open-circuit voltage across the gap is responsible, and thus the systems are often classified as such 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported extraordinary transmission from one-dimensional (1-D) sub-wavelength slits instead of holes from the microwave to the UV range. [9][10][11][12][13][14] However, narrow slits do not behave like cylindrical apertures. The former is dominated by the transverse electric magnetic (TEM) waveguide mode propagating inside the slits.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5, the dispersion curves of the structure are represented, with the [18] as the propagation vector for this loop is given by the TEM mode of the slits q z = k w . The modes of f 13t behave as dielectric core and metallic cladding waveguide modes, but phase shifted as it includes a propagation inside the metallic slit as well as the propagation inside the dielectric bounded by metallic layers.…”
Section: Transmission In the Subwavelength Regime With A Thick Dielecmentioning
confidence: 99%
“…The theoretical model presented here uses the coupled mode theory in the multiple scattering formalism [17][18][19][20][21]. The structure studied in this paper consists in a dielectric layer of thickness h 2 , in between two corrugated metallic layers of thicknesses h 1 and h 3 .…”
Section: Scattering Coefficientsmentioning
confidence: 99%